Inventions and Scientific Discoveries Of Andalusian Scholars - Sotvoldiyev, Oybek (Pubmedia Social Sciences and Humanities, 2024)
This article discusses the inventions and scientific discoveries made by Andalusian scholars in various fields of science. The scientific environment in which these scholars flourished, the works they authored, the influence of these works on subsequent generations of scientists, and the contemporary significance of the Andalusian scholars’ scientific heritage are analyzed. Special attention is also given to female Andalusian scholars.